Peran media sosial dalam pembentukan dan pemeliharaan identitas nasional - putri, sofiyah amalun (Maliki Interdisciplinary Journal, 2025)
The use of technology and social media has become an inseparable part of everyday life, this study analyzes the dual role of social media in the formation and maintenance of national identity, focusing on its positive and negative impacts. Social media has been shown to facilitate the spread of information and culture, strengthen the sense of nationhood and encourage online citizen participation. However, the spread of inaccurate information (misinformation and disinformation), increasing political polarization and manipulation of digital identity also pose serious threats to the integrity of national identity. The data analysis technique in this study uses a qualitative descriptive method to investigate the positive and negative impacts of social media, and provides policy recommendations to maximize benefits and minimize risks to national identity.